SARS-CoV-2 Vaccine-Induced Humoral Immunity in Immunocompetent European Adults: A Systematic Review - Izabella Bylica; Estera Jachowicz-Matczak; Justyna Brodowicz; Joanna Sułkowska; Monika Bociąga-Jasik; Piotr Heczko; Sebastian Gagatek; Jan Bylica; Jadwiga Wójkowska-Mach (Microorganisms)
The COVID-19 pandemic, caused by SARS-CoV-2, profoundly impacted global health systems and economies. Vaccination and diagnostic advancements were pivotal in managing the pandemic. This systematic review evaluates antibody levels in adults following complete COVID-19 vaccination and examines the prevalence of infections in vaccinated populations. A systematic review adhering to PRISMA guidelines was conducted, focusing on studies analyzing antibody levels at least 14 days after full vaccination with FDA- or EMA-approved vaccines. Five European studies meeting the inclusion criteria were selected. Data were extracted and synthesized from studies involving 6280 participants aged 19 to 105, with an average of 11% having prior exposure to SARS-CoV-2. Antibody levels were analyzed over time, and the incidence of post-vaccination COVID-19 cases was recorded. The reviewed studies demonstrated that antibody levels peaked shortly after vaccination but gradually declined over time. Individuals with prior SARS-CoV-2 infection exhibited higher antibody titers than those without prior exposure. After the first dose, the Pfizer–BioNTech vaccine led to significantly higher antibody levels than the Oxford–AstraZeneca vaccine, especially in those without prior infection. Across all studies, the incidence of COVID-19 among vaccinated individuals was low (0.1–3.8% for 144–302 days post-vaccination). Vaccination reduced severe outcomes despite decreasing antibody levels. The decline in new COVID-19 cases and related deaths is attributed to widespread vaccination, natural immunity, and virus mutations reducing severity. Further studies are warranted to explore antibody persistence and optimal vaccination strategies.